The Effect of Shopee's Payment Methods and Twin Date Promotions on Shopping Decisions on the Shopee Application - muhammad zieo Addefrid putra; Tri Inda Fadhila Rahma; Nursantri Yanti (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
In the current digital age, rapid technological progress has significantly reshaped consumer behavior, especially within the e-commerce sector. Shopee stands out as a prominent e-commerce platform, maintaining a strong presence in the digital marketplace by offering diverse payment options and engaging promotional campaigns, particularly targeting younger consumers. This research seeks to examine the impactIn the current digital age, rapid technological progress has significantly reshaped consumer behavior, especially within the e-commerce sector. Shopee stands out as a prominent e-commerce platform, maintaining a strong presence in the digital marketplace by offering diverse payment options and engaging promotional campaigns, particularly targeting younger consumers. This research seeks to examine the impact of payment methods and double-date promotional events on purchasing decisions made through the Shopee application by students at he State Islamic University of North Sumatra (UINSU). The study was conducted within the Faculty of Islamic Economics and Business, involving a sample of 100 students selected through a probability sampling method. Employing a quantitative approach, data were gathered using a Likert-scale questionnaire. Multiple linear regression analysis was applied to interpret the data. Findings indicate that the availability of various payment methods on Shopee positively influences consumer purchasing decisions. Moreover, Shopee's double-date promotional strategies also contribute positively to purchase intentions, particularly among users within the Faculty of Islamic Economics and Business at UINSU of payment methods and double-date promotional events on purchasing decisions made through the Shopee application by students at he State Islamic University of North Sumatra (UINSU). The study was conducted within the Faculty of Islamic Economics and Business, involving a sample of 100 students selected through a probability sampling method. Employing a quantitative approach, data were gathered using a Likert-scale questionnaire. Multiple linear regression analysis was applied to interpret the data. Findings indicate that the availability of various payment methods on Shopee positively influences consumer purchasing decisions. Moreover, Shopee's double-date promotional strategies also contribute positively to purchase intentions, particularly among users within the Faculty of Islamic Economics and Business at UINSU.